KONTROL SOSIAL WALI KELAS PADA PELANGGARAN TATA TERTIB SISWA KELAS XI IPS DI SMA NEGERI 1 KECAMATAN SUBAH KABUPATEN SAMBAS - Emon, Monika; Zakso, Amrazi; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this research is to find out how the homeroom teacher's preventive and repressive social control on violations of the rules of class XI students at SMA Negeri 1 Subah. The research was conducted using a descriptive qualitative approach. In collecting data techniques used are observation, interviews, and documentation. The data sources used are primary data sources and secondary data sources where the main data sources in qualitative research are words and actions, the rest are additional data such as documents and others. In analyzing the data using data reduction techniques, data presentation, and drawing conclusions. The results of the study show that the homeroom teacher's preventive social control for violations of the rules is by giving verbal warnings such as giving directions or advice, giving written warnings, making letters or agreements with the students concerned to prevent violations of the rules from occurring. The purpose of preventive control is to direct, persuade or remind not to commit the violations. Meanwhile, the homeroom teacher's repressive social control on violations of the rules is by giving punishment according to the violations they have committed in the form of picking up trash, push-ups, giving letters of reprimand or summons to students who are absent from school more than three times in a row. The purpose of giving this punishment is to make the party who behaves deviant aware of the consequences of this deviation, as well as so that he obeys social norms.